2001
DOI: 10.1007/s004280100465
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy case of pulmonary capillary hemangiomatosis without evidence of pulmonary hypertension

Abstract: We report a case of pulmonary capillary hemangiomatosis (PCH) affecting a 37-year-old woman. PCH is a rare disease accompanying intrapulmonary capillary growth and pulmonary hypertension. In the present case, capillaries infiltrated the alveolar and bronchial walls but not the vascular walls. No signs or symptoms of pulmonary hypertension or right heart hypertrophy/dilatation were present. These findings suggest that vascular involvement in PCH is responsible for the induction of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…Havlik et al 9 found incidental PCH-like foci in 5.7% of autopsy cases without any symptoms of PH; the distribution of the foci was local and the patients were old men, so that may be a different entity from PCH, which affects young adults of both sexes and has diffuse histopathological changes. Umezu et al 10 reported an autopsy case of PCH without any evidence of PH in which proliferation of capillaries was observed in the alveolar and bronchial walls, but not in the vascular walls; however, most patients with PCH, including the present case, have PH and related symptoms because of the diffuse proliferation of capillaries. Because PCH is a rare disorder, it is not clear at this point whether PCH without PH represents an early stage of PCH or is a different class of PCH.…”
Section: Discussionmentioning
confidence: 48%
“…Havlik et al 9 found incidental PCH-like foci in 5.7% of autopsy cases without any symptoms of PH; the distribution of the foci was local and the patients were old men, so that may be a different entity from PCH, which affects young adults of both sexes and has diffuse histopathological changes. Umezu et al 10 reported an autopsy case of PCH without any evidence of PH in which proliferation of capillaries was observed in the alveolar and bronchial walls, but not in the vascular walls; however, most patients with PCH, including the present case, have PH and related symptoms because of the diffuse proliferation of capillaries. Because PCH is a rare disorder, it is not clear at this point whether PCH without PH represents an early stage of PCH or is a different class of PCH.…”
Section: Discussionmentioning
confidence: 48%
“…Haemangiomatosis-like foci and distinct local manifestations can cause diagnostic difficulties [18,19]. PH (in certain instances PPH) is generally (but not in all cases) regarded as a 'sine qua non' prerequisite of the diagnosis of PCH [4,27,42,47,49,52]. The WHO classification [39] differentiates five categories of PH: (1) pulmonary arterial hypertension, (2) pulmonary venous hypertension, (3) PH associated with disorders of the respiratory system and/or hypoxaemia, (4) PH due to chronic thrombotic and/or embolic disease, and (5) PH due to disorders directly affecting the pulmonary vasculature [13,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although this nonspecific symptom is a clinical manifestation of PCH, it is also found with inflammatory alveolitis caused by the CREST syndrome, which was also included in our differential diagnosis. In the setting of primary pulmonary hypertension, the presence of hemoptysis, pleural effusion, elevated number of iron-laden bronchoalveolar macrophages, and an interstitial radiological pattern suggest PCH [2,4,5,6], though there has been at least one report in which pulmonary hypertension was absent in the presence of PCH [6], adding to the difficulty in diagnosing this rare disease. Retrospective analysis of a report by Humbert et al [4] demonstrated that the clinical presentation of PCH is indistinguishable from that of classic hypertensive pulmonary arteriopathy.…”
Section: Discussionmentioning
confidence: 99%